Human Rights: A Promising Perspective for Business & Society. Issue 5 (May 2022) - Schrempf-Stirling, Judith; Van Buren, Harry J.; Wettstein, Florian
In his invited essay for Business & Society's 60th anniversary, Archie B. Carroll (2021, p. 16) refers to human rights as "a topic that holds considerable promise for CSR [corporate social responsibility] researchers in the future." The objective of this article is to unpack this promise. We (a) discuss the momentum of business and human rights (BHR) in international policy, national regulation, and corporate practice, (b) review how and why BHR scholarship has been thriving, (c) provide a conceptual framework to analyze how BHR and corporate social responsibility (CSR) relate to each other, and (d) provide a research agenda outlining how BHR can expand business and society scholarship in general and one of its foundational constructs, CSR, in particular, beyond the current confines of the business and society field.